The use of google earth as the learning media in geosciences education - Islami, Nur (Journal of Educational Sciences, 2018)
In studying geosciences, students sometimes face some problemsbecause occasionally they are not able to visualize the earth in their minds.This difficulty is increasingly moreover, if it concerns the distance andheight of the topography of the earth, as well as the earth and its relationshipto all aspects of life. In this study, the use of google earth as the learningmedia has been examined to help students understanding in learninggeosciences. Students were given guidelines of google earth usage and thenstudents were asked to create a mini project in terms of using of googleearth. After that students were given a questioner that is questioned aboutunderstanding of the learned material with the help of google earth. Theresults show that almost all students are fully aware of what they are doing.They also gave an average score of 3.8 (scale 4) in terms of the google earthutilities in learning geosciences. It can be concluded that google earth is ableto provide a deeper understanding to the students in studying the concept ofphysics of earth.